2022
DOI: 10.3389/fcvm.2022.819915
|View full text |Cite
|
Sign up to set email alerts
|

Plausible Functional Diagnostics by Rational Echocardiography in the Assessment of Valvular Heart Disease - Role of Quantitative Echocardiography in the Assessment of Mitral Regurgitation

Abstract: The echocardiographic assessment of valvular heart diseases is the basic analysis of valvular defects next to clinical investigation and stethoscopy. Severity of mitral regurgitation (MR) is usually estimated by an integrated approach using semi quantitative parameters and is still one of the biggest challenges of echocardiography. Quantitative echocardiographic analysis of MR severity often fails to describe comprehensible hemodynamic conditions. However, comprehensive echocardiography based on standardized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Plausible explanations for lower cardiac volumes by native 2D echocardiography in comparison with 2D contrast and native 3D echocardiography as well as with cardiac MRI in the clinical setting [ 55 , 57 , 58 ] are methodological errors due to foreshortening or differing contour delineations of the endocardium and limitations due to spatial resolution. In contrast to these previous studies, recent communications and trials using modern ultrasound technologies showed that comprehensive echocardiography can provide reliable and verifiable cardiac volume measurements by planimetry/volumetry as well as by Doppler echocardiography to correctly characterize cardiac hemodynamics [ 18 , 59 62 ]. In conclusion, using a definitive quantitative approach to grade the severity of valvular regurgitation includes the acceptance of the requirements to properly and plausibly determine LV volumes by echocardiography.…”
Section: Introductionmentioning
confidence: 99%
“…Plausible explanations for lower cardiac volumes by native 2D echocardiography in comparison with 2D contrast and native 3D echocardiography as well as with cardiac MRI in the clinical setting [ 55 , 57 , 58 ] are methodological errors due to foreshortening or differing contour delineations of the endocardium and limitations due to spatial resolution. In contrast to these previous studies, recent communications and trials using modern ultrasound technologies showed that comprehensive echocardiography can provide reliable and verifiable cardiac volume measurements by planimetry/volumetry as well as by Doppler echocardiography to correctly characterize cardiac hemodynamics [ 18 , 59 62 ]. In conclusion, using a definitive quantitative approach to grade the severity of valvular regurgitation includes the acceptance of the requirements to properly and plausibly determine LV volumes by echocardiography.…”
Section: Introductionmentioning
confidence: 99%